2017
DOI: 10.3389/fmicb.2017.02000
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Basis of Stationary Phase Survival and Applications

Abstract: Stationary phase is the stage when growth ceases but cells remain metabolically active. Several physical and molecular changes take place during this stage that makes them interesting to explore. The characteristic proteins synthesized in the stationary phase are indispensable as they confer viability to the bacteria. Detailed knowledge of these proteins and the genes synthesizing them is required to understand the survival in such nutrient deprived conditions. The promoters, which drive the expression of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
164
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(187 citation statements)
references
References 89 publications
9
164
0
2
Order By: Relevance
“…The productions of proteins at stationary phase may be linked with the need of the bacterium to combat complex environments present in the stationary phase including altered pH and osmolality. It has been reported that the production of proteins at stationary phase increased by 121% as compared with exponential phase (Ou et al, 2004;Jaishankar and Srivastava, 2017). The release of amino acids in this study may relate to peptidoglycan synthesis and quorum-sensing system (De Kievit et al, 2001;Aliashkevich et al, 2018).…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…The productions of proteins at stationary phase may be linked with the need of the bacterium to combat complex environments present in the stationary phase including altered pH and osmolality. It has been reported that the production of proteins at stationary phase increased by 121% as compared with exponential phase (Ou et al, 2004;Jaishankar and Srivastava, 2017). The release of amino acids in this study may relate to peptidoglycan synthesis and quorum-sensing system (De Kievit et al, 2001;Aliashkevich et al, 2018).…”
Section: Discussionmentioning
confidence: 52%
“…This clearly indicated that regardless of alterations in environmental factors applied in this study, the different phases of growth inferred the most influence on uptake characteristics. Stationary phase is considered as a complex environment, and physiologically is comparable to biofilm (Jaishankar and Srivastava, 2017). In stationary phase, extraordinary adjustments take place including morphological, physiological changes and DNA/protein ratio was found to be higher (Nystrom, 2004;Jaishankar and Srivastava, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the stationary phase, prokaryotes undergo several morphological and physiological changes that increase their stress resistance and allow them to survive under severe nutrient restrictions. These include the development of smaller and spherical cells, a rigid cell envelope, nucleoid condensation, a reduction in protein synthesis, and an increase in peptidases/proteases . Very few studies have explored the transition to stationary phase at a global scale in Archaea and to the best of our knowledge, only two have done it at the proteome level: in the thermophile Thermococcus kodakarensis and H. marismortui …”
mentioning
confidence: 99%
“…Additionally, induction usually takes place in the exponential growth phase of the bacterial culture. In this phase, overexpression of proteins increases the metabolic burden of each cell and proteins which are detrimental for bacterial growth cannot be produced in some cases (Jaishankar and Srivastava, ). These disadvantages could be circumvented by using auto‐inducing expression strategies for recombinant protein production.…”
Section: Introductionmentioning
confidence: 99%